Implementasi Model Pembelajaran Problem Solving Untuk Meningkatkan Motivasi Belajar Dan Hasil Belajar Pkn Siswa - Ni Kadek Putus Sasrini (Jurnal Ilmiah Sekolah Dasar, 2018)
This study aims to ( 1 ) increase students' motivation to learn civics and ( 2 ) improving student learning outcomes of the implementation of civic education learning model of Problem Solving in learningÂ  civics . The subjects were VIÂ  grade students of SD Negeri 6 Tianyar in the second semester of academic year 2016/2017 , amounting to 35 men with 20 men and 15 women . This research was conducted in two cycles of learning with the stages in each cycle includes planning , action , observation / evaluation , and reflection . The data were collected by the method of student motivation questionnaire and student learning outcomes data collected through charging student worksheets ( LKS ) , tasks, quizzes , and a final test cycle . The collected data were then analyzed descriptively . Results showed ( 1 ) an increase in the average score of student learning moivasi at 87.80 on the first cycle and the second cycle increased to 92.74 , ( 2 ) an increase in civics student learning outcomes in the first cycle was 76.8 with complete categories and on the second cycle increased to 80.7 with complete categories.